STUDY OF METHANOL AND DME PROCESS PRODUCTION FROM COAL GAS SYNTHESIS RESULTS - Reksaning Adhi, Fajar
One candidate for a substitute for petroleum-based fuels is dimethyl ether (DME). LPG imports in Indonesia are projected to increase to 13.2 million tonnes in 2050. DME can be used as a mixture of LPG because it has physical properties that resemble LPG. Apart from the ever-increasing imports of LPG, the need for methanol every year in Indonesia is also increasing. The coal downstream program is a program to convert coal into final products, namely methanol and DME. Methanol and DME synthesis technology is divided into two methods. The direct synthesis method is carried out in one step, namely from the synthesis gas directly to DME (model-1). The indirect synthesis method is a two-stage synthesis technology of methanol synthesis followed by methanol dehydration to produce DME (model-2). These two synthesis methods have been widely studied by several process technology licensors such as JFE Group, Haldor Topsoe, TEC, and Lurgi. The purpose of this research is to conduct a techno-economic study for two models of methanol and DME production processes. The aspects studied in this study are expected to help, especially for coal mining producers to be able to implement the coal downstream program as a program for converting coal into final products such as DME. The selection of technology is conducted by group discussions with members of the laboratory of the thermofluid and system utility ITB and advisers who are indeed expertise in this field. The wto types of production process flow resulting from the selection of this technology will be compared based on technical aspects and economic aspects to get the most suitable production process flow. The equilibrium reactor modeling to resemble a real reactor can be validated using a known feed base whose product composition is known. The validation results to obtain value of temperature approach to equilibrium (?Tap). The parameter values will follow the equation for the reaction involved. The ?Tap parameters for methanol synthesis and methanol dehydration reaction were -20.21 and 10.17 ?. Evaluation of the effect of variable operating conditions on process performance parameters is needed to determine the optimum operating conditions. The effect of temperature has a tendency for the lower the better and vice versa for the effect of pressure. The optimum operating conditions for model-1 are a temperature of 200 ?, a pressure of 45 bar, and a recycling ratio of 0.65. Meanwhile, for model-2, the temperature is 200 ?, pressure is 75 bar, and the recycling ratio is 0.7 This study uses Aspen HYSYS process simulation software as a tool to obtain comparison parameters for the type of production process flow. Economic evaluation is carried out based on the minimum feasibility estimate for class V with an accuracy of -30% / + 50% using Excel and Aspen Icarus software to obtain comparative parameters in economic aspects. Overall CO conversion can be achieved for both models up to 97%. The yield of DME for model-1 is 15,7% and for model-2 is 20,5%. The daily production of DME for model-1 reached 34.9 tons and for model-2 was 46.2 tons. The heat demand per DME product in MMBtu produced for model-1 is 9.0 and for model-2 is 10.3. The electricity demand per DME product in kW for model-1 is 14.9 and for model-2 is 15.1. The capital value for model-1 is 9.37 million USD and for model-2 is 8.72 million USD. Operating costs per tonne of DME product are 210 USD for model-1 and USD 147 for model-2. The IRR eligibility parameter for model-1 is 21.37% with NPV of 8.66 million USD and for model-2 is 68.54% with NPV of 28.82 million USD